Social Interaction With an Anonymous Opponent Requires Increased Involvement of the Theory of Mind Neural System: An fMRI Study - Zheltyakova, Maya; Korotkov, Alexander; Masharipov, Ruslan; Myznikov, Artem; Didur, Michael; Cherednichenko, Denis; Wagels, Lisa; Habel, Ute; Kireev, Maxim; Votinov, Mikhail (Frontiers in Behavioral Neuroscience, 2022)
An anonymous scenario might facilitate provoking behaviour and modify the engagement of theory of mind (TOM) brain mechanisms. However, the effect of anonymity when processing provoking feedback remains largely unknown. The current fMRI study applied the Taylor aggression paradigm, introducing an anonymous opponent to this task. Thirty-nine healthy right-handed subjects were included in the statistical analysis (13 males/26 females, mean age 24.5 ± 3.6 years). During the task, a player winning the reaction-time game could subtract money from the opponent, which was viewed as a social provocation. While participants behaved similarly to both introduced and anonymous opponents, during the perception of a provocation from an anonymous opponent (when compared to the introduced opponent), the right inferior frontal gyrus (IFG) demonstrated an increased BOLD signal and increased functional connectivity with the left IFG. Further, increased functional connectivity between the right IFG and brain regions—including the right temporal parietal junction and precuneus—was observed during the perception of high provocation (subtracting a large amount of money) from the anonymous opponent compared to the introduced opponent. The obtained results point to the increased engagement of the TOM neural system as a compensatory mechanism during social interactions that lack socially relevant information.